Fungsi Bantuan Hukum Dan Perlindungan Hak Tersangka Dalam Proses Penyidikan - Rio Praswahyu; M. Syahrul Borman; Moh. Taufik (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the function of legal aid and the protection of suspects' rights during the investigation process within the Indonesian criminal justice system. The right of suspects to obtain legal assistance is part of human rights protection guaranteed by legislation, particularly the Indonesian Criminal Procedure Code (KUHAP). However, in practice, violations of suspects' rights are still frequently found, such as intimidation, violence, and the lack of awareness among suspects regarding their right to legal representation. This research employs a normative legal research method using a statutory approach by examining various laws and regulations related to legal aid and the protection of suspects' rights. The results of the study indicate that legal aid plays an important role in ensuring access to justice, realizing equality before the law, and protecting suspects’ rights during the investigation process. Furthermore, the protection of suspects can be implemented through several legal mechanisms, including the assistance of legal counsel, the application of the presumption of innocence principle, and the use of pretrial institutions to examine the legality of investigators’ actions. Therefore, the existence of legal aid becomes an essential instrument in realizing a fair criminal justice process and ensuring the protection of suspects' rights.